Influência da matriz urbana na estrutura de redes de interação planta-visitante floral em fragmentos de vegetação campestre do Sul do Brasil - Neves, Mariana Beal (2018)
Mutualistic relationships between plants and animals play a key role in ecological and evolutionary processes. These relationships are seen as complex networks of interaction, which present recurrent structural patterns and are severely threatened by anthropogenic factors. The objective of this work was to evaluate the influence of the isolation caused by urbanization on the interaction networks between plants and floral visitors. Twelve South Brazilian fragments were sampled in the metropolitan area of Porto Alegre, Rio Grande do Sul. Sampling was performed during spring and summer of 2016/17 in 1-hectare circular plots using the focal method (10 minutes observation / plant). We estimated the degree of isolation of the fragments by calculating the area covered by urban matrix in a buffer of 2000 meters around each plot. We performed a qualitative-quantitative sampling of vegetation as part of the explanatory data observed for the network patterns. To construct interaction matrices, we divide visitors into potential pollinators and non-pollinators. We construct quantitative interaction matrices for each fragment/plot by calculating the metrics available in the networklevel function of the bipartite package of the R program. We estimate the correlation between the logarithm of the urbanized area in a radius of 2000 meters and each network metric calculated with the generalized linear model. We sampled 1240 plants (182 species). The total abundance of floral visitors was 1840 specimens (94% potential pollinators). The richness of plant species was greater in areas more isolated by urbanization, which is due to the fact that these areas catch fire more frequently. The richness of visitors was also higher in these areas, which is due to a "bottom up" effect given by the increase in plant richness. The results suggest that networks increase connectance and nestedness (in more urbanized areas) as a way of protection against the disturbance, increasing system stability. In addition, areas further away from urbanization allow a greater level of network specialization, since they have a greater range of niches. We conclude that these findings highlight the importance of investing in the conservation and maintenance of natural areas within large cities, although they may seem isolated in the midst of a dense urban matrix. These areas are still a good haven for wildlife and need to be kept intact.